Evaluation Of Impact Of Guideline Adherence, Associated Risk Factors On Mortality And Functional Disability And Direct Costs Of In-Hospital Care In Patients With First-Ever Acute Ischemic Stroke - Mohammed, Mustapha (2023)
This study aimed to assess the impact of guideline adherence on stroke outcomes, develop and validate prediction models based on the guidelines, and evaluate the direct medical costs of in-hospital care for patients with their first-ever acute ischemic stroke. The study was a multi-centered observational cohort study involving adult patients with their first-ever acute ischemic stroke who received care at participating clinical centers of the Malaysian National Stroke Registry (NSR).